2017
DOI: 10.1001/jamainternmed.2017.1246
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary Embolism and Deep Venous Thrombosis in Patients Hospitalized With Syncope

Abstract: Drs Verma and Masoom had full access to all of the data in the study and take responsibility for the integrity of the data and the accuracy of the data analysis. Drs Verma and Masoom are co-first authors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
23
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 7 publications
5
23
1
Order By: Relevance
“…We demonstrated a low diagnostic rate of PE at both index ED visit and over a 180‐day follow‐up. This result was in line with previous studies, which found the rate of PE to be <1.5% . Despite the low prevalence, 15.7% of all patients underwent D‐dimer testing, and 7.2% had CTPA performed.…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…We demonstrated a low diagnostic rate of PE at both index ED visit and over a 180‐day follow‐up. This result was in line with previous studies, which found the rate of PE to be <1.5% . Despite the low prevalence, 15.7% of all patients underwent D‐dimer testing, and 7.2% had CTPA performed.…”
Section: Discussionsupporting
confidence: 93%
“…were Caucasian (reflecting demographics in the geographic area) ( The rate of PE in patients with syncope in our study is in agreement with several other studies [10][11][12][13]15 and is much lower than the rate found in the PESIT trial. However, the rates of testing for PE were not reported in these studies, suggesting the possibility of underascertainment.…”
Section: Methodssupporting
confidence: 92%
See 3 more Smart Citations